2002
DOI: 10.1103/physrevlett.89.072301
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-Nucleus Potential inA=28

Abstract: We have studied the (pi(-),K+) reaction on a silicon target to investigate the sigma-nucleus potential. The inclusive spectrum was measured at a beam momentum of 1.2 GeV/c with an energy resolution of 3.3 MeV (FWHM) by employing the superconducting kaon spectrometer system. The spectrum was compared with theoretical calculations within the framework of the distorted-wave impulse approximation, which demonstrates that a strongly repulsive sigma-nucleus potential with a nonzero size of the imaginary part reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(21 citation statements)
references
References 19 publications
5
16
0
Order By: Relevance
“…potentials are much less attractive than the nucleonic ones, reflecting the weaker strength of the NY compared to the NN potentials. Within the ESC08 model, the well-depths U (k = 0) in normal nuclear matter of the , , and hyperons are, respectively, −39, +16, −8 MeV, and thus in reasonable agreement with current experimental estimates of these quantities [20,21]. The partial wave decompositions of these values are given in Table III which also lists explicitly the contributions of the different (isospin) channels according to Eqs.…”
Section: A Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…potentials are much less attractive than the nucleonic ones, reflecting the weaker strength of the NY compared to the NN potentials. Within the ESC08 model, the well-depths U (k = 0) in normal nuclear matter of the , , and hyperons are, respectively, −39, +16, −8 MeV, and thus in reasonable agreement with current experimental estimates of these quantities [20,21]. The partial wave decompositions of these values are given in Table III which also lists explicitly the contributions of the different (isospin) channels according to Eqs.…”
Section: A Resultssupporting
confidence: 76%
“…This serves to connect the NN, NY, and YY channels and is utilized to make a simultaneous fit to the NN and NY data with a restricted set ( 20) of free coupling constants, etc., see [8] for details. In particular, the BBM coupling constants are calculated via SU(3), using, together with the meson mixing angles, the fitted constants in the NN ⊕ NY analysis as input.…”
Section: The Nijmegen Esc08 Potentialmentioning
confidence: 99%
“…[12]. Both changes are expected to stiffen the resulting EOS and could thus possibly allow larger maximum masses of hyperon stars than found before, for the following reasons: The ESC08b YN potential features in particular a repulsive − N interaction in agreement with recent experimental indications [19], and in contrast to the previously used YN potentials. Therefore a smaller − fraction is now expected in β-stable matter.…”
Section: Introductionsupporting
confidence: 80%
“…The Λ binding energy of Λ-hypernuclei is well reproduced by an attractive Woods-Saxon potential of depth - (Millener et al 1988). The analyses of the (π − , K + ) reaction data on medium to heavy nuclei (Noumi et al 2002) performed in Harada & Hirabayashi (2006) and Kohno et al (2006) revealed a moderately repulsive Σ-nuclear potential in the nuclear interior of around 10-40 MeV, while the fits to Σ − atomic data (Friedman & Gal 2007) indicate a clear transition from an attractive Σ potential in the surface, to a repulsive one in the interior, although the size of the repulsion cannot be precisely determined. As for the strangeness −2 systems, the Nagara event (Takahashi et al 2001) and other experiments providing consistency checks established the size of the ΛΛ interaction to be mildly attractive, (Dover & Gal 1983), while the missing-mass spectra of the -+ K K , ( ) reaction on a 12 C target suggest a milder attraction of −20 MeV (Fukuda et al 1998) or ∼−14±2 MeV (Khaustov et al 2000).…”
Section: Hyperons and Magnetic Fieldmentioning
confidence: 86%